2002
DOI: 10.1095/biolreprod66.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Expression of Anticoagulant Heparan Sulfate Proteoglycans and Serine Protease Inhibitors in the Rat Ovary: A Potent System of Proteolysis Control1

Abstract: During the reproductive cycle, ovarian follicles undergo major tissue-remodeling involving vascular changes and proteolysis. Anticoagulant heparan sulfate proteoglycans (aHSPGs) are expressed by granulosa cells during the development of the ovarian follicle. The function of aHSPGs in the ovary is unknown, but they might be involved in proteolysis control through binding and activation of serine protease inhibitors. To identify functional interactions between aHSPGs and heparin-binding protease inhibitors in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 56 publications
4
29
4
Order By: Relevance
“…We demonstrate that during the periovulatory period the expression of PN-1 is initially upregulated by hCG, and then declines in a pattern similar to the expression of PAI-1 and tPA. This profile of PN-1 expression appears to differ from that observed in rodents, where no change in expression was observed until the onset of ovulation (Hägglund et al 1996, Hasan et al 2002, although these are in situ studies that do not lend themselves well to quantification. We also demonstrate a potential role for PN-1 in dominant follicular growth, as follicular protein levels are higher in non-atretic than in early-atretic and atretic follicles.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…We demonstrate that during the periovulatory period the expression of PN-1 is initially upregulated by hCG, and then declines in a pattern similar to the expression of PAI-1 and tPA. This profile of PN-1 expression appears to differ from that observed in rodents, where no change in expression was observed until the onset of ovulation (Hägglund et al 1996, Hasan et al 2002, although these are in situ studies that do not lend themselves well to quantification. We also demonstrate a potential role for PN-1 in dominant follicular growth, as follicular protein levels are higher in non-atretic than in early-atretic and atretic follicles.…”
Section: Discussioncontrasting
confidence: 63%
“…In mice, granulosa cell PN-1 expression generally did not vary throughout the periovulatory period (Hägglund et al 1996), although a decrease in immunostaining was observed 12 h after hCG injection in PMSG-stimulated rats (Hasan et al 2002). The present data clearly show a transient upregulation of PN-1 expression within 6 h of hCG treatment, indicating that PN-1 regulation in cattle is different from that of rodents.…”
Section: Follicle Classcontrasting
confidence: 46%
See 2 more Smart Citations
“…Again, no effect on the rate of ovulation was observed. Because there are a multitude of proteolytic enzymes present within the ovary during the periovulatory period (Chun et al 1992;Liu et al 1997;Hasan et al 2002), it is likely that the lack of any effect of these antagonists on oocyte release is due to rapid degradation of these peptide-based antagonists in vivo. However, given the results reported herein, the requirement for EDNRB-mediated signalling in the process of ovulation needs to be re-evaluated.…”
Section: Discussionmentioning
confidence: 99%